Clinical, Anamnestic and Microbiological Criteria for Diagnosis of Septic Complications in Children with Purulent-destructive Diseases - L.F. Pritulo (Zaslavsky O.Yu., 2012)
There were investigated clinical, anamnestic and microbiological criteria for diagnosis of septic complications in 220 children with an acute destructive pneumonia, in 110 - with an acute hematogenous osteomyelitis and in 114 - with acute peritonitis. The bacterial analysis in suppurative focus of infection has shown, that depending on specific type of microflora the most severe course is observed in patients with gram-negative flora and its associations. To prevent the development of severe complications of septic diseases in children it's necessary to assess risk factors at different levels of health care delivery.